Предмет: Алгебра,
автор: 20071958MJ
Теңдеуді шешіңіз:
( х +4)(х -3)-( х-5)(х+2)= 6.
Ответы
Автор ответа:
4
Ответ:
х = 2
Объяснение:
( х +4)(х -3)-( х-5)(х+2)= 6.
х² -3х+4х-12 -(х² +2х-5х-10) -6=0
х² -3х+4х-12 -х² -2х+5х+10 -6=0
4х - 8=0
4х= 8
х = 8÷4
х = 2
Проверка
( 2 +4)(2 -3)-( 2-5)(2+2)= 6
6·(- 1) - (-3)·4 =6
-6 +12 =6
6 =6
20071958MJ:
Спасибо большое!
Похожие вопросы
Предмет: Русский язык,
автор: SakinaM8
Предмет: Русский язык,
автор: rimmamus
Предмет: Русский язык,
автор: abylxanovam
Предмет: Физика,
автор: Al7ina2d
Предмет: Математика,
автор: Викториядарц